2011
DOI: 10.1063/1.3620419
|View full text |Cite
|
Sign up to set email alerts
|

On-chip collection of particles and cells by AC electroosmotic pumping and dielectrophoresis using asymmetric microelectrodes

Abstract: The recent development of microfluidic "lab on a chip" devices requiring sample sizes <100 lL has given rise to the need to concentrate dilute samples and trap analytes, especially for surface-based detection techniques. We demonstrate a particle collection device capable of concentrating micron-sized particles in a predetermined area by combining AC electroosmosis (ACEO) and dielectrophoresis (DEP). The planar asymmetric electrode pattern uses ACEO pumping to induce equal, quadrilateral flow directed towards … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
32
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 46 publications
(34 citation statements)
references
References 36 publications
2
32
0
Order By: Relevance
“…Additionally, since this frequency is generally above 20 kHz, ACEO is not apparent. Conversely, studies on optimization of trapping percentage using a combination of ACEO and DEP have generally been performed in the absence of pressure driven background flow [19][20][21][22][23]. With the advent of pressure driven flow, maximum throughput may be increased but the convection of the particles from the edge of the electrodes -where the field gradient is at a maximum -to their center is expected to result in a drop in the trapping percentage as the hydrodynamic force can more easily dominate the weakened DEP [24].…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, since this frequency is generally above 20 kHz, ACEO is not apparent. Conversely, studies on optimization of trapping percentage using a combination of ACEO and DEP have generally been performed in the absence of pressure driven background flow [19][20][21][22][23]. With the advent of pressure driven flow, maximum throughput may be increased but the convection of the particles from the edge of the electrodes -where the field gradient is at a maximum -to their center is expected to result in a drop in the trapping percentage as the hydrodynamic force can more easily dominate the weakened DEP [24].…”
Section: Introductionmentioning
confidence: 99%
“…The unique flow structure induced by ACEO enables particles to concentrate into a certain location in a microchannel with electrode array. Previous studies (Bhatt et al 2005;Lian et al 2006;Melvin et al 2011) have discussed the effectiveness of particle concentration by ACEO around electrodes located at limited positions in the fluidic channel. They confirmed that ACEO could collect particles toward a specific zone on electrode depending on the geometry of the electrode array.…”
Section: Introductionmentioning
confidence: 98%
“…Many alterative actuation mechanisms have been proposed to achieve a pumping effect in microfluidic devices, including acoustic-wave-based, rotary, piezoelectric, thermopneumatic, electrostatic, electromagnetic and ferrofluidic methods [16][17][18][19][20][21]. Recently, Lee's group [22][23][24][25] developed an impedance-based micro pump based on electromagnetic actuation and including a copper microcoil, a glass microchannel, a glass cover plate and a PDMS diaphragm with a magnet mounted on its upper surface.…”
Section: Introductionmentioning
confidence: 99%